Volatile Organic Compounds of Anchote Tuber and Leaf Extracted Using Simultaneous Steam Distillation and Solvent Extraction - Yenenesh Ayalew; Dargie Tsegay Berhe; Nigusse Retta; Gulelat Desse; Ali Mohammed; Kyong Su Kim (International Journal of Food Science)
Anchote (Coccinia abyssinica (Lam.) (Cogn)) is an endemic and potentially valuable crop of Ethiopia principally categorized under root and tuber crops, and its newly growing leaves along with the tendrils are also used as nutritious vegetable served after being cooked. Leaf and tuber powders were extracted for the first time to identify volatile organic compounds by simultaneous steam distillation and solvent extraction (SDE) and characterized using gas chromatography mass spectrometry (GC-MS). VOCs having an area percentage above 0.5% were used for identification analysis. From the results, thirty volatile flavor compounds from leaves and fifteen from tubers were identified with the total fraction yield of 770.57 mg/kg and 4536.91 mg/kg, respectively, and from the 30 compounds identified from leaf 16 were distinguished in each of the tested accessions. Ethyl acetate 90.47% (697.13 mg/kg) was detected in a higher amount exhibiting >1% peak area. The rest 6.03% (46.46 mg/kg) were minor quantities (<1%) of the total (770.57 mg/kg) volatile flavor fraction. Among the 15 identified compounds in the tuber, ethyl acetate was the only major compound that accounted together for 99.15% (4498.33 mg/kg) of the total volatile flavor fraction and 0.85% (38.58 mg/kg) being reported in minor quantities (<1%). The SDE extraction and GC-MS analysis of anchote leaves and tubers successfully identified various volatile flavor compounds, which indicates that anchote was found to be a potential source of volatile flavor compounds that can be used as a food flavoring agent and in folk medicines. Thus, this study confirms that anchote leaf and tuber can be used for more specific and valuable applications in food and medicine industries.